La comunicación audiovisual del programa infantil veo veo de la televisión pública Ecuador TV y el desarrollo cognitivo de los niños y niñas de 1 a 5 años de edad en el Centro de Desarrollo Infancia Universitaria - González Torres, Rosa Magaly (2015)
The audiovisual communication of children's educational programs in the media of the small screen, today have the need to contribute to the overall content learning, impregnated in a fun and entertaining context, educating about current social problems, taking into account children spend more time in front of a TV and are the most vulnerable audience. In order to obtain the information required for the fulfillment of the objectives several parent surveys were conducted as well as interviews with nursery teachers Development Center "Children's University", the information was statistically analyzed and interpreted. The population or a universe that was taken into account for the realization of this research was five teachers and 80 parents of children who are educated and cared for in the aforementioned center. With the information gathered was reached to obtain different conclusions regarding the habits that have infants at the time of viewing your favorite programs. This was proposed to develop a proposal to try to solve the problem of this research giving great importance to the audiovisual communication of the children's series on the cognitive development of infants, enabling them to actively participate in its growth and training. Keywords: Learning, skills, educational, emotional, playful.